An Improved Round Robin Scheduling Algorithm For Enhancing CPU Utilization (The International Journal of Engineering & Information Technology (IJEIT), 2024)
CPU scheduling is the first goal and most important section of any operating system. CPU Scheduling algorithms are the methods or strategies which help scheduler to choose process in the ready queue. One of those strategies is Round Robin scheduling algorithm, a big challenge in this algorithm is how to adapt dynamic time quantum to be suitable for all of processes allocated in the ready queue, thus achieve making the best use of CPU. In this paper, a model was built in which a dynamic time quantum calculated by using average and standard deviation formula executed first, then use slice time to perform the first cycle and next cycle until the ready queue becomes empty. By applying this idea, the average turnaround time, waiting time could be minimized and the throughput of the CPU could be maximized and compare the proposal algorithm with three modifications of Round Robin algorithm which modified in recent years. a pre-modified round robin algorithm (DevRR) was modified, a model standard deviation round robin algorithm (SDRR) was developed, where the slice time using statistical measures was calculated and a simulation with Java Eclipse Version 2021-12 (4.22.0) and JDK operating environment (16.0.1) was built, to see whether the experimental results meet my requirements or not? And our modified algorithm using three scheduling criteria was implemented and evaluated, where were the average waiting time, the average turnaround time, and the throughput rate.